2021
DOI: 10.1002/app.50698
|View full text |Cite
|
Sign up to set email alerts
|

Confined batch foaming of semi‐crystalline rubbery elastomers with carbon dioxide using a mold

Abstract: Confined foaming of poly(ethylene-co-vinyl acetate-co-carbon monoxide) using carbon dioxide as a physical blowing agent in a mold with either permeable or impermeable boundaries has been explored as a strategy to control final foam dimensions and morphology. The results are discussed in terms of comparisons to free-foaming experiments conducted at the same pressure and temperature conditions following the same pressurization and depressurization paths. Foaming experiments were carried out at 30 and 40 C and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Many activities have been done to improve the mechanical properties of PLA, but these actions do not meet the requirements of industrialization due to the type of process. [58][59][60] The incorporation of CNF into the PLA foam matrix has been reported in some studies. In these studies, the effect of CNF on the strain and viscosity of PLA foams has been investigated and it has been concluded that CNF reduces cell size and also increases cell density and foam density.…”
Section: Introductionmentioning
confidence: 99%
“…Many activities have been done to improve the mechanical properties of PLA, but these actions do not meet the requirements of industrialization due to the type of process. [58][59][60] The incorporation of CNF into the PLA foam matrix has been reported in some studies. In these studies, the effect of CNF on the strain and viscosity of PLA foams has been investigated and it has been concluded that CNF reduces cell size and also increases cell density and foam density.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently increased interest in the use of CO 2 as a blowing agent due to the mentioned safety and environmental reasons, as well as cost considerations [36,43,73,74]. The main drawback of its use is its higher diffusivity than that of long-chain hydrocarbons such as pentane, which affects the maximum expansion ratio achievable [32], the thermal aging of the foam [75], and can cause post-foaming shrinkage [72,76,77]. Strategies to overcome this will be discussed in Section 4.2.2.…”
Section: Selection Of Raw Materials: Need For Materials Characterizationmentioning
confidence: 99%
“…CO 2 is a suitable blowing agent given its high solubility and produced plasticization, which allows to foam at lower temperatures and supports the stabilization step when the plasticization is lost upon desorption [45]. However, the shrinkage and collapse of the cellular structure of the resulting foams due to its high diffusivity in the hot polymer matrix are problematic, in particular with low rigidity [71,72] and elastomeric [76,77] polymers. A long-established strategy to overcome this has been the use of long chain hydrocarbons as blowing agents [57,136].…”
Section: Processing Strategies Towards Cell Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also many scientific reports in the literature on the adaptation of the manufacturing process to obtain porous structures with the appropriate properties. An ideal summary of the considerations concerning the influence of the mold shape on the foam properties was made in [ 45 ].…”
Section: Introductionmentioning
confidence: 99%